Economic indicators for automobile claim frequencies; Indicadores económicos para las frecuencias de siniestralidad de automóviles - Eva Boj; Anna Casta\~ner; Maria Mercè Claramunt; Teresa Costa; Oriol Roch (Estudios de Economía, 2019)
This article examines the relationship between observed claim frequencies in the automobile insurance line and the evolution of selected economic magnitudes. From a variety of economic variables, we aim to identify the main factors affec - ting claim frequencies, while controlling for other legislative and demographic factors. Through a dynamic regression model, the analysis is conducted for three different categories of vehicles and for a variety of coverages. A comprehensive dataset from the main Spanish insurance companies is used to calibrate the model. The evidence might assist companies to improve ratemaking.
Keywords: C10; C53; E32; 330; Categories of vehicles; dynamic regression; external predictors; motor insurance; time series